Asymmetry changes in sprinting do not relate to changes in sprint performance - Gleadhill, S.; Nagahara, R. (International Journal of Sports Science & Coaching, 2025)
This study considers asymmetry during dynamic human movement as any biomechanical differences between left and right sides of the body. Previous studies have reported spatiotemporal and ground reaction force (GRF) asymmetries during sprint running and jumping tasks but have not found any associations between asymmetry and sprinting performance, however, have cross-sectionally examined asymmetry at only a single point in time. Therefore, the importance of asymmetry fluctuations across time or training sessions in relation to sprint performance changes remain unclear. The aim was clarifying whether changes in asymmetry of leg extension performance, measured by single-leg countermovement jumps (CMJ), influence fluctuations in sprinting asymmetry, and whether any such fluctuations are associated with changes in maximal running speed. Thirteen sprinters performed maximal effort 60-m sprints on a long force platform system and single-leg CMJs across two testing sessions, one month apart. Pearson's correlation coefficients were calculated to examine the relationships between the changes in spatiotemporal and GRF asymmetry across sessions with either the changes in CMJ asymmetry or changes in maximum running speed. Results demonstrated that small fluctuations in asymmetry occurred between sessions but were not significantly associated with sprint performance or CMJ asymmetry changes. Therefore, asymmetry may not need to be prioritised in periodic testing as a key performance indicator, and these findings provide valuable insight for coaches, suggesting that training should focus on known sprint determinants rather than minimising asymmetry. Moreover, asymmetry during sprinting may not necessarily relate to asymmetry of leg extension strength in non-injured well-trained sprinters.